Food crops information systems in Kabupaten Karo (rice and pulses) - Gunawan Simon Purba; Saipun Bahri Daulay; Adian Rindang; Riswanti Sigalingging (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Food crops information systems in Kabupaten Karo (rice and pulses), still manual/conventional and still less effective and in efficient. To overcome the inferiority, we need a system that can deliver the information in a timely and accurately. Information systems in food crops (rice and pulses) web-based solution that is right. Information systems web-based food commodities was containing information about the condition and potential of  food crops. The system was designed based on the  user needs using the PHP programming language, MySQL database and the web Apache web server using rapid application development (RAD), which was a very short development method with quick application technique